Cereal extrusado, free glúten, formulado com subprodutos de arroz e quinoa - Godoy, Roberta Camargo de (2013)
Rice is considered a staple food in many parts of the world. A cause for concern is the rice breakdown during milling processes and these broken grains are not generally accepted by consumers. The rice industry generates a lot of waste, and broken grains of rice and bran. These products can be blended with certain desired ingredients to improve its quality for preparing extruded grains such as "snacks". With environmental concerns, issues related to hunger and waste is important to study the utilization of these residues with the use of available technology. The aim of this study was to develop extruded cereal in natural flavors, sweet and savory, from the broken grains of rice bran and rice with quinoa, evaluate their physico-chemical, microbiological and sensorial acceptance. There was no microbial contamination of the final product with none of the microorganism studied, namely coliform at 45 ° C, Salmonella, Staphylococcus aureus, Bacillus cereus, molds and yeasts. For sensory evaluation showed that the salty snack earned the highest score for all criteria: overall (6.5), flavor (6.5), crispness (7.2), on a scale 1-9. To purchase intention, the result was 3.5 on a scale of 1 to 5. The use of rice cereal gluten-free, is an alternative to the industrial sector, which can be applied in developing various products for human consumption.